Acute Hypertriglyceridemia Induces Platelet Hyperactivity That is Not Attenuated by Insulin in Polycystic Ovary Syndrome. Issue 1 (28th February 2014) - Aye, Myint Myint; Kilpatrick, Eric S.; Aburima, Ahmed; Wraith, Katie S.; Magwenzi, Simbarashe; Spurgeon, B.; Rigby, Alan S.; Sandeman, Derek; Naseem, Khalid M.; Atkin, Stephen L.
Abstract : Background: Atherothrombosis is associated with platelet hyperactivity. Hypertriglyceridemia and insulin resistance (IR) are features of polycystic ovary syndrome (PCOS). The effect of induced hypertriglyceridemia on IR and platelet function was examined in young women with PCOS. Methods and Results: Following overnight fasting, 13 PCOS and 12 healthy women were infused with saline or 20% intralipid for 5 hours on separate days. Insulin sensitivity was measured using a hyperinsulinemic euglycaemic clamp in the final 2 hours of each infusion. Platelet responses to adenosine diphosphate (ADP) and prostacyclin (PGI2 ) were measured by flow cytometric analysis of platelet fibrinogen binding and P‐selectin expression using whole blood taken during each infusion (at 2 hours) and at the end of each clamp. Lipid infusion increased triglycerides and reduced insulin sensitivity in both controls (median, interquartile range ) (5.25 [3.3, 6.48] versus 2.60 [0.88, 3.88] mg kg −1 min −1, P <0.001) and PCOS (3.15 [2.94, 3.85] versus 1.06 [0.72, 1.43] mg kg −1 min −1, P <0.001). Platelet activation by ADP was enhanced and ability to suppress platelet activation by PGI2 diminished during lipid infusion in both groups when compared to saline. Importantly, insulin infusion decreased lipid‐induced platelet hyperactivity by decreasing their response to 1 μmol/L ADP (78.7% [67.9, 82.3] versus 62.8% [51.8, 73.3], P =0.02) and increasing sensitivity to 0.01 μmol/L PGI2 (67.6% [39.5, 83.8] versus 40.9% [23.8, 60.9], P =0.01) in controls, but not in PCOS. Conclusion: Acute hypertriglyceridemia induced IR, and increased platelet activation in both groups that was not reversed by insulin in PCOS subjects compared to controls. This suggests that platelet hyperactivity induced by acute hypertriglyceridemia and IR could contribute athero‐thrombotic risk. Clinical Trial Registration: URL: www.isrctn.org. Unique Identifier: ISRCTN42448814.